Normal CT Anatomy, Morphometry, and Volumetry of the Skull in Urial Sheep (Ovis vignei) - Omid Zehtabvar; Majid Masoudifard; Javad Abbasi; Seyyed Hossein Modarres Tonekabony; Amin Zamani (Veterinary Medicine International)
The urial (OOR-ee-əl; Ovis vignei), also known as the arkars or shapo, is a wild sheep native to Central and South Asia. It is listed as vulnerable on the International Union for Conservation of Nature (IUCN) Red List. Considering the importance of this breed in the world and its extinction, there is a need to determine the anatomy of the head area or any other disease such as fractures, dental, and infectious diseases. Five adult healthy male urial sheep were used, which were mature in terms of age. After preparation, the fresh alive sheep were immediately examined using a helical computed tomography scanner. The morphometry of the skull of this sheep was studied using RadiAnt application. The volume calculation was performed automatically using the software available on the CT scan system (Syngo MMWP VE40A software). The sinuses observed in the skull of this breed included frontal, maxillary, lacrimal, palatine, and sphenoidal sinuses. The height, length, and width of the skull were measured as 15.32 ± 0.05, 23.89 ± 0.08, and 12.57 ± 0.05 cm, respectively. According to the results obtained from the volume of different parts of the head in urial sheep, the nasal cavity and the oral cavity constitute 7% and 6% of the head volume, respectively. This ratio was calculated as 0.5% in the case of the inner and middle ears. Determining the anatomical structures and morphometric and volumetric characteristics of Urial sheep, which is one of the endangered Asian breeds, was of particular importance in order to prepare the head and skull atlas.